2015
DOI: 10.1155/2015/607432
|View full text |Cite
|
Sign up to set email alerts
|

TrypanosomaInfection Rates inGlossinaSpecies in Mtito Andei Division, Makueni County, Kenya

Abstract: African Animal Trypanosomiasis (AAT) transmitted cyclically by tsetse fly (Glossina spp.) is a major obstacle to livestock production in the tropical parts of Africa. The objective of this study was to determine the infection rates of trypanosomes in Glossina species in Mtito Andei Division, Makueni County, Kenya. Tsetse fly species, G. longipennis and G. pallidipes, were trapped and DNA was isolated from their dissected internal organs (proboscis, salivary glands, and midguts). The DNA was then subjected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
5
9
0
1
Order By: Relevance
“…This finding corroborates previous studies in which these two savannah tsetse species were found to be predominant in the Maasai Mara-Serengeti ecosystem of Kenya and Tanzania [43–45]. As both species are competent vectors of human and animal trypanosomes [46,47], their presence highlights the persistent risk of AAT and HAT in the MMNR. Despite their lower abundance relative to G. pallidipes, G. swynnertoni had higher rates of infection with trypanosomes, underpinning its critical role in transmission of African trypanosomes as demonstrated by previous studies [48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding corroborates previous studies in which these two savannah tsetse species were found to be predominant in the Maasai Mara-Serengeti ecosystem of Kenya and Tanzania [43–45]. As both species are competent vectors of human and animal trypanosomes [46,47], their presence highlights the persistent risk of AAT and HAT in the MMNR. Despite their lower abundance relative to G. pallidipes, G. swynnertoni had higher rates of infection with trypanosomes, underpinning its critical role in transmission of African trypanosomes as demonstrated by previous studies [48].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, T. vivax usually achieves higher parasitemia in hosts than do T. congolense and T. brucei , further increasing its chances of being transmitted to tsetse flies during blood-feeding on infected hosts [54]. Infection rates were similar for both female and male tsetse flies, as found in another recent study conducted in Mtito Andei, Kenya [47].…”
Section: Discussionmentioning
confidence: 82%
“…Since only one G. pallidipes specimen was captured, no accurate discussion can be presented on the infection rate of this species. However, in other studies, Trypanosoma infection were detected in G. pallidipes [31,98], which shows that they can actively harbor and transmit trypanosomes. The presence/absence of infection in tsetse flies can be due to feeding preferences [99], genetic differences, the availability of reservoirs, the parasitaemia of the vertebrate host [100,101] and the nutritional status of the flies [102,103].…”
Section: Discussionmentioning
confidence: 75%
“…The use of trapping to determine the distribution of hematophagous insects have been extensively described in the scientific literature [28][29][30][31][32][33]. Currently, a plethora of different traps are available for collecting hematophagous brachyceran flies.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes mamíferos domésticos e selvagens podem servir como hospedeiros e há um grande número de espécies e subespécies de moscas tsé-tsé envolvidas na transmissão destes parasitas. T. congolense é altamente prevalente em hospedeiros de importância econômica como ovinos, caprinos, bovinos e suínos (Adams et al, 2010b) assim como em moscas tsé-tsé (Nthiwa et al, 2015;Isaac et al, 2016).…”
Section: Subgênero Nannomonasunclassified